Finger Prosthetic Design Based in the Anatomy and Biomechanics Studies - Andres Pavajeau, Oscar F. Avilés, Ruben Hernández, Edilberto Mejia (International Journal of Advanced Science and Technology, 2020)
The objective of this work is to demonstrate the methodology used to obtain a robotic system with anthropomorphic characteristics of the index finger of the hand, through the characterization and biomechanical study of kinematic parameters, in order to obtain a mechanism that generates movement of the robotic finger. For the development of robotic finger prosthesis, an anatomical study of the hand is analyzed, integrating the Denavit-Hartenberg method to represent the dynamics of finger movement. Considering the above, the selection of materials that most resembled the behavior of the tendons was made and stress tests were carried out on each of the materials to see which one performs better for the robotic prosthesis. Also, a study of drive and motor methods for the design of the prosthesis. Once the mechanical design of the prosthesis is carried out, the selection of the electronics and the characterization of the elements that comprise it are made, facilitating the connection with the Matlab® software in which a user interface was designed to replicate the movement of the human finger through the SimMechanics plugin. Obtaining as result the development of the robotic finger prosthesis simulating the movements in 90%, complying with the proposed parameters.